Idea sharing: some thoughts on Chinese and Malaysian popular writing instructions - Zhai, Xiuwen; Razali, Abu Bakar; Sulaiman, Tajularipin; Luo, Shengyao (ASR Research India, 2022)
More and more Chinese students have been studying at university campuses in Malaysia to earn their postgraduate degrees. As the largest group of international students, academic writing in English is a problem for Chinese international postgraduates at English-medium instruction (EMI) campuses overseas. When pursuing their degrees at an English Medium Instruction (EMI) campus, postgraduate students' writing ability has an important impact on their studies.Those studying writing instruction in higher education are dedicated to identifying how writing instructions influence EFL/ESL learners' academic writing ability. Still, few studies review the kinds of writing instructions with samples of EFL/ESL students earning a master's or doctoral degree (i.e., postgraduate students) especially in the context of Chinese international students studying in Malaysian higher education institutions, which is one of the most popular destinations for Chinese international postgraduate students. A review of studies on writing instructions for EFL/ESL for Chinese international students in the Malaysian context is presented in this article. The authors report of the problems in the application of writing strategies during language instruction for Chinese EFL/ESL students. The authors address the concerns regarding teaching approaches to writing and suggest ways to prevent issues in the future regarding the implementation of teaching approaches in EFL/ESL writing for international Chinese students. To help all Malaysian and Chinese educators improve the quality of writing instruction, the authors encourage educators to explore the effectiveness of genre-based approaches for teaching academic writing in their countries.